SISTEM INFORMASI BERBASIS WEB UNTUK MONITORING PENCAPAIAN KOMPETENSI MAHASISWA PADA KURIKULUM BERBASIS KOMPETENSI - , ALOYSIUS AIRLANGGA BAJUADJI; , Dr. Ir. Lukito Edi Nugroho, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Higher education applying competence-based curriculum needs to administer a good teaching and learning process in order to prepare the students to have qualified competences. Therefore, it is needed to monitor the studentsâ achievements. This research, thus, was conducted to design a system for monitoring the achievements of the studentsâ competences. Each step of the studentsâ progress was and will always be processed by the system to find out whether a student has accomplished the targeted competences. The competences indicated the academic achievements of a certain student in fulfilling a competence-based curriculum. The data was gathered by applying software engineering designs and models, especially web engineering. The fist step was collecting primary and secondary data by administering library research. The primary data was the scheme of the competence-based curriculum, the list of main subjects, sub-competences, skills, and group-competence subjects. Whereas the secondary data was about the students, teachers, subjects/curriculum, study plan, semester transcript, and transcript taken from the available academic information system. The next step was a need analysis by using interview technique to determine the indicators of the needs. Once the needs were found, an information system for monitoring the achievements of the studentsâ competences was designed. This system was a web-based using PHP language programing and MySQL database. The system was tested by continually applying independent Unit Testing to ensure the possibility of bug appearance. Once the system was ready to be applied, Acceptance Testing was used by the users to assess whether the outcome has met with their needs. The research result was a web-based information system for monitoring the achievements of the studentsâ competences in a competence-based curriculum. The users of the system are students, academic advisers, and academic officers (the head of department). The system produced 6 functions of monitoring the achievements of competences. They are the study progress, subjectsâ distribution based on competence-based curriculum scheme, main competences, sub-competences, skills, and group of competences.